A Halal Lifestyle on Muslim Fashion Development In The Perspective of Satr Al-Awrah: The Analysis at Tamrin City Mall Jakarta - bin Lahuri, Setiawan; Sutarman, Zhifanny Prafitasari; Zuhroh, Ainun Amalia (Universitas Al-Qolam Malang, 2025)
This research aims to examine the halal lifestyle changes in Muslim fashion sold in the mall, and the affects consumers' perception of halal products based on how the concept of ‘Satr Al-Awrah’ was implemented on muslim fashion product. Thamrin City Mall was chosen as the research location as the largest shopping centre for Muslim fashion in Indonesia. However, some transformations are considered to violate sharia principles, especially related to the provision of covering the awrah. The research method used is qualitative with a field study approach. This research collects data through in-depth interviews with producers, consumers and sellers of Muslim fashion clothing in Thamrin City mall, the analysis is carried out with reference to the concept of satr al-awrah as a basic principle in dressing according to sharia, which is studied in the context of market dynamics and modern culture. The results show that despite the aesthetic improvement and innovation in Muslim fashion at Thamrin City Mall, considered a problem, especially when modern designs prioritise visual appeal over religious observance. These results indicate that despite the challenges in maintaining the balance between fashion and religious values to maintain sharia principles of Muslim fashion in Indonesia. This research provides recommendations to manufacturers to create products that remain relevant in the global market while maintaining religious values. Also educating consumers about the importance of sharia-compliant Muslim fashion as part of the halal lifestyle.